Digital Branding Strategies for Tourism Destinations in Luwuk Banggai: Challenges and Opportunities - Wahyudin Rahman; Pardin Lasaksi; Sutrisno K Djawa (CV. Creative Tugu Pena, 2026)
This study analyzes the digital branding strategies used to promote tourism destinations in Luwuk Banggai and examines the challenges and opportunities that shape their implementation. Materials and Methods: A qualitative descriptive design was employed. Data were gathered through semi-structured interviews, field observations, documentation, and analysis of tourism-related social media content. Participants represented the tourism office, destination management, local tourism businesses, content creators, and domestic tourists. The material was analyzed thematically through familiarization, coding, categorization, theme development, cross-source comparison, and interpretation. Results: Instagram and TikTok were the most intensively used platforms because they supported visual storytelling, short-form video, rapid circulation, and direct audience interaction. Branding practices centered on destination photography, reels, short videos, captions, hashtags, and user-generated content. At the same time, the findings revealed a visibility–capability gap: strong platform adoption was not yet matched by consistent brand identity, coordinated editorial planning, professional content production, digital marketing competence, promotional resources, or reliable connectivity. Opportunities arose from expanding social media use, visitor-created content, influencer partnerships, digital tourism behavior, and community participation. Conclusions: Digital branding can strengthen the visibility and competitiveness of Luwuk Banggai, but sustainable results require an integrated destination identity, differentiated platform roles, systematic content governance, stronger human-resource capacity, improved infrastructure, and collaboration among public, private, community, and creator stakeholders. The study contributes a contextual explanation of how regional destinations can achieve high online visibility while still facing limited institutional branding capacity.